Relevansi Penentuan Arah Kiblat dengan Data Rasi Bintang dalam Kitab Suwar Al-Kawakib - Alawiya, Balkis Sifara; Ahmad, Izzuddin (Universitas Islam Negeri Mataram, 2023)
The Fixed Star Book, also known as Suwar Al-Kawakib, is one of the most significant pieces of medieval Arabic astronomy literature. Around 964 AD, Persian astronomer Abdul-Rahman Al-Sufi wrote it. Ptolemy's Almagest is referred to in Al-Sufi's work, which incorporates a thorough star list and definite star diagrams for every one of the 48 old style heavenly bodies. This article discusses how to use data from the constellations in the Suwar Al-Kawakib, or book of fixed stars, to determine the direction of Qibla. In this research article, the author tries to connect the information in the fixed star book about the direction of the Qibla and the constellations. According to the book, it makes sense that the Little Bear heavenly body (Ursa Minor) is the group of stars closest to the north pole. Al Farqadain and al-Juday are Arab names for the two brightest stars in this constellation. The position of Al-Juday, which is the brightest star at the tail's end, is used to find the Qibla, or the direction of Mecca. This investigation aims to determine whether one of the stars mentioned in Suwar Al-Kawakib can be measured to determine the Qibla's direction, however in this time the relevance of north star or polaris in determinin the direction of Qobla is considered a form of folk astronomy with sufficient precision the tolerance of Qibla deviation.